(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: The freshwater snail Parafossarulus manchouricus serves as the critical biological link in the transmission cycle of the small liver fluke (Clonorchis sinensis), a pressing public health issue in Vietnam. This study aims to identify bioclimatic factors limiting the species’ distribution and construct an epidemiological risk map using an ecological modeling approach. Methods: We applied an Ensemble Species Distribution Modelling (SDM) approach, combining four machine learning algorithms (Maxnet, GLM, MARS, Random Forest), to analyze data from 279 occurrence points in Northern Vietnam alongside bioclimatic variables. Results: The model achieved excellent predictive performance with an AUC value of 0,983. The results indicate that the distribution of P. manchouricus is strongly governed by three factors: Mean Diurnal Range (Bio2), Min Temperature of Coldest Month (Bio6), and Precipitation of Driest Month (Bio14). High-risk hotspots were identified along the coastal regions of the Red River Delta and North Central Coast, comprising Ninh Binh, Nam Dinh, Hai Phong, and Quang Ninh provinces, with an estimated core area of approximately 11.490 km². Conclusion: This risk map provides a quantitative scientific basis for preventive health authorities to prioritize surveillance in identified hotspots. Control strategies should focus on managing aquaculture environments and implementing biological control measures in areas with high ecological suitability indices to interrupt the transmission cycle to humans